(untitled) (Vietnam Journal of Community Medicine, 2024)
Taking care of infected surgical wounds helps patients quickly heal the surgical wound and to reduce the time to treatment. Aims: Evaluate the results of care for infected surgical wounds by Negative pressure wound therapy. Patients and methods: 30 patients with infected surgical wounds were cared for by Negative pressure wound therapy at the Department of digestive surgery, Viet Duc university hospital, from 3/2020 to 7/2021. Results: The rate of superficial infection was 66,7%, and the rate of deep infection was 33,3%. The rate of clean surgery was 3,3%, clean-contaminated surgery was 60,0%, contaminated surgery was 33,3%, and infected surgery was 3,3%. In 30 patients with infected surgical wounds treated by Negative pressure wound therapy: 4 days (93.3%), 8 days (6.7%). The results of taking care of infected surgical wounds: 76,7% of patients were recovered and discharged from the hospital, 23,3% of patients had a reduction of wound infection and were transferred to a local hospital, the average time of hospitalization after surgery was 11,7 ± 3,9 days. Conclusions: The technics of care for infected surgical wounds by Negative pressure wound therapy are feasible and effective in treating surgical wound infection.